ITIKAD BAIK DALAM PERJANJIAN JUAL-BELI TANAH MENURUT KUH-PERDATA - Ashar Sinilele (El-Iqthisadi, 2020)
AbstractArticle 1338 paragraph 3 of the Civil Code, states that an agreement must be carried out in good faith. Good faith when making an agreement means honesty, then good faith in the implementation stage, namely, the agreement is appropriateness, namely an assessment of the behavior of a party in implementing what was agreed. In the sale and purchase agreement, especially the sale and purchase of land, it is hoped that a balance can be created between the two parties concerned, one of which is good faith between each other which is also expected to create a conducive atmosphere. According to article 1362 of the Civil Code and Article 1383 of the Civil Code, there is a difference between the presence or absence of good faith on the party receiving the payment. Article 1360 of the Civil Code, states that whoever, in good faith, has received something that does not have to be paid to him, is obliged to return it with interest and the proceeds, calculated from the payment and thus does not reduce the compensation for costs, losses and interest, if the price is already suffer a slump. If his goods have been destroyed, even though this happens beyond his fault, then he is obliged to pay the price accompanied by compensation for interest, loss and price, unless he can prove that the goods were also destroyed, if he is in the person to whom he should have been given.  Keywords: Agreement, Good Faith, Land, Sale and Purchase. AbstrakPasal 1338 ayat 3 KUH Perdata, menyatakan bahwa suatu perjanjian harus dilaksanakan dengan itikad baik. Itikad baik pada waktu membuat suatu perjanjian berarti kejujuran, maka itikad baik dalam tahap pelaksanaan yaitu, perjanjian adalah kepatutan yaitu suatu penilaian terhadap tindak tanduk suatu pihak dalam hal melaksanakan apa yang diperjanjikan. Dalam perjanjian jual-beli terkhususnya jual-beli tanah sangatlah diharapakan dapat tercipta keseimbangan antar kedua belah pihak yang bersangkutan, salah satunya itikad baik antar sesama yang juga diharapkan dapat tercipta suasana yang kondusif. Menurut pasal 1362 KUH Perdata dan pasal 1383 KUH Perdata dibedakan antara ada atau tidaknya itikad baik dipihak yang menerima pembayaran. Pasal 1360 KUH Perdata, menyatakan bahwa siapa yang dengan itikad baik, telah menerima sesuatu yang tidak harus dibayarkan kepadanya, diwajibkan mengembalikan dengan bunga dan hasil-hasilnya, terhitung dari hasil pembayaran dan demikian itu tidak mengurangi penggantian biaya, rugi dan bunga, jika harganya telah menderita kemerosotan. Jika barangnya telah musnah, meskipun ini terjadi diluar salahnya, maka ia wajib membayar harganya dengan disertai penggantian bunga, rugi dan harga, terkecuali jika ia dapat membuktikan bahwa barang itu musnah juga, seandainya ia berada pada orang kepada siapa ia seharusnya diberikan.Kata Kunci : Itikad Baik, Jual Beli, Perjanjian, Tanah.